Aplicación de la metodología STEAM en el proceso Enseñanza-Aprendizaje de los estudiantes del colegio de Bachillerato Abdón Calderón Muñoz de la parroquia Santiago, cantón y provincia de Loja, en el año lectivo 2022-2023. - Villavicencio Guamán, Nancy Marisol (2023)
This research work analyzes the STEAM methodology in the teaching-learning process from the perspective of the students of the High School Abdón Calderón Muñoz of the parish Santiago of the Loja city in the school year 2022-2023, therefore, The methodology used for the development and fulfillment of the research was the deductive method, with quantitative approach, being descriptive in scope and with a cross-sectional design, taking into account that 45 high school students were taken as population, where the STEAM methodology and its application in the teaching-learning process were described, through bibliographic sources, such as articles, scientific bases and third level theses; Then, the application of the STEAM methodology in the teaching-learning process of the students of the present institution was diagnosed through a survey organized in phases which are challenge, research, creation and communication. The purpose of this survey is to know if it promotes the technical-scientific and artistic training, with a different, integrative and transversal approach, through active methodologies that promote the development of critical, creative, reflective, logical thinking and cognitive processes. Keywords: STEAM, Teaching-Learning, Project-based learning, Cooperative learning